03 Tractography to visualise the relationship of the optic radiation to epileptogenic lesions prior to neurosurgery. Issue 3 (15th February 2011) - Winston, G P; Yogarajah, M; Symms, M R; McEvoy, A; Micallef, C; Duncan, J S
Abstract : Background: A third of patients with epilepsy are refractory to medical treatment and may be amenable to surgery. A major concern is to avoid causing new deficits. As conventional MR imaging does not delineate the optic radiation, the risk to vision from surgery cannot be predicted, nor can surgery be tailored to minimise the risk. Methods: Conventional structural MRI and diffusion tensor imaging were acquired in 13 patients with medically refractory epilepsy due a lesion near the optic radiation and undergoing pre-surgical evaluation at the National Hospital for Neurology and Neurosurgery. The optic radiation was delineated and visualised in relation to the lesions on anatomical images and in 3D reconstructions. Pre- and post-operative visual fields were acquired by Goldmann perimetry. Results: The relationship between the epileptogenic lesion and the optic radiation was demonstrated in each patient provididing helpful additional information in deciding whether to proceed with surgery, and in planning the surgical procedure and approach. Prseoperative and postoperative imaging findings correlated with the visual field data. Conclusion: The optic radiation shows significant anatomical variability, but can be reliably delineated by tractography. As surgical disruption of the optic radiation has serious consequences for the patient, DTI tractography proves a useful technique in this population. Future integration with real-time neuronavigation will minimise the risks of neurosurgery.